2006
DOI: 10.1111/j.0906-6705.2006.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

In situ profiling and quantification of cytokines released during ultraviolet B‐induced inflammation by combining dermal microdialysis and protein microarrays

Abstract: In skin, an evolving inflammatory or immune response is triggered by early release of a cytokine cascade into the extracellular space. Investigation of extracellular cytokine secretion in situ has been limited by low cut-off filtering membranes and sample volume size and the inability to monitor changes in cytokine protein levels in real-time in situ. Here, we combine for the first time the methods of intradermal microdialysis and antibody protein arraying to profile the early cascade of multiple cytokines in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
60
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 46 publications
5
60
0
Order By: Relevance
“…Comparison of HAS1, HAS2 and HAS3 mRNA levels revealed that HAS2 gene expression levels are higher than HAS1 and HAS3, whereas HYAL2 gene expression predominates over HYAL1, which is consistent with a similar study by Averbeck et al (2006). In comparison of HAS mRNA levels among NHDFs derived from differently aged donors, while fibroblasts from the oldest donor (77NHDF) have the lowest levels of HAS1, HAS2 and HAS3 mRNAs at all culture time points, two kinds of NHDFs from younger donors (0NHDF and 19NHDF) have the highest mRNA levels of HAS1, HAS2 and HAS3 at all culture time points with mRNA levels similar to each other.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Comparison of HAS1, HAS2 and HAS3 mRNA levels revealed that HAS2 gene expression levels are higher than HAS1 and HAS3, whereas HYAL2 gene expression predominates over HYAL1, which is consistent with a similar study by Averbeck et al (2006). In comparison of HAS mRNA levels among NHDFs derived from differently aged donors, while fibroblasts from the oldest donor (77NHDF) have the lowest levels of HAS1, HAS2 and HAS3 mRNAs at all culture time points, two kinds of NHDFs from younger donors (0NHDF and 19NHDF) have the highest mRNA levels of HAS1, HAS2 and HAS3 at all culture time points with mRNA levels similar to each other.…”
Section: Discussionsupporting
confidence: 92%
“…In relation to the age-dependent impairment in wound healing, aging fibroblasts have a defect in their phenotypic maturation that is required for tissue remodeling and the closure of wounds because of the dysfunction of HA-dependent CD44/epidermal growth factor receptor signaling. The cellular mechanisms of UVB-induced changes in HA in skin cells and tissues have been studied in detail (Südel et al 2005;Averbeck et al 2006;Dai et al 2007;Röck et al 2011), and it has been shown that the loss of HA is closely associated with phenotypic characteristics of skin photo-aging (Margelin et al 1996;Takahashi et al 1995Takahashi et al , 1996. In contrast, the effects of chronological aging on HA are much less well understood.…”
Section: Discussionmentioning
confidence: 99%
“…In the translation of findings to the human (clinical) in vivo situation, the main methods of obtaining data have been peripheral blood, which summates effects at a whole organism level, and skin biopsy, which gives tissue-specific (skin) data on the presence of or gene induction for the production of a protein at the specific time point the biopsy was taken. Cutaneous microdialysis (CMD) enables continuous in vivo sampling of the interstitial fluid in the intact skin and is thus an attractive, newer and arguably less tissue destructive alternative for the measurement of cytokines actually present in the dermal extracellular environment over a period commensurate with the expected pathogenesis of the reaction under study (6)(7)(8)(9)(10)(11). The present study is on normal skin and combines CMD with end point biopsy for immunohistochemistry of the actual microdialysis area to compare the findings of the two methodologies at a specific time point, 24 h.…”
Section: Introductionmentioning
confidence: 99%
“…17 Therefore both direct effects of UVB on fibroblasts in the papillary dermis and indirect effects through UVB-mediated responses in epidermal keratinocytes such as changes in gene expression, growth factor, and cytokine release must be considered. 18 In addition, acute and chronic consequences of UVB irradiation must be distinguished. Acutely, UVB causes sunburn and transient inflammatory reactions.…”
mentioning
confidence: 99%